Integrasi Sains dan Agama dalam Paradigma Filsafat Pendidikan Islam - Sumiyati Sumiyati; NURUL HAYATI; Safitrianingsih; Febry Suprapto (Educational Research Center, 2026)
The dichotomy between science and religion is an epistemological issue that continues to characterise modern education systems, including those in the Muslim world. The influence of a secular Western educational paradigm has encouraged a separation between empirical knowledge and spiritual–religious values, resulting in a moral crisis and a reduction in the meaning of education. This article aims to analyse the concept of integrating science and religion within the paradigm of Islamic educational philosophy as an effort to develop a holistic and balanced educational system. This study employs a qualitative approach, using library research and content analysis of relevant primary and secondary sources drawn from both classical Islamic intellectual traditions and contemporary thought. The findings indicate that Islamic educational philosophy inherently rejects the dichotomy of knowledge and affirms the unity of the sources of knowledge based on the principle of tawḥīd. The integration of science and religion in Islamic education harmoniously combines reason, revelation, and empirical experience, and directs knowledge towards the formation of individuals who are knowledgeable, morally upright, and socially responsible. Theoretically, this research contributes to strengthening an integrative epistemology of Islamic education, while practically it provides a conceptual foundation for the development of curricula, educational policies, and value-oriented learning practices. This study affirms the relevance of Islamic educational philosophy in addressing global educational challenges in the modern